Marketing e produtos sustentáveis: estudo de caso da Philips no Brasil - Silva, Lucia Lucena de A. e (2008)
The subjects sustainable development and climate change have become recurrent in our daily life and are no longer specific issues of scientists and researchers. Companies have begun to change many of their processes in order to meet environmental demands made by governments and consumers. Two points of major concern are: the way these goods are produced and the impacts they cause to the environment, society and economy. Based on the theories of Marketing, Consumer Behavior, Social Responsibility, Product Development and Analysis of Environmentally Product Life Cycle, it was possible to determine important issues for which a product is considered environmentally responsible. Understanding these concepts, a case study was made in the company Philips, in Brazil, and its line of products from Lighting Home. The objective of this study was to analyze and evaluate the concepts and practices, and to verify if the fluorescent lamps may or may not be considered green products